Adherence to healthy lifestyle factors and risk of death in men with diabetes mellitus: the Physicians’ Health Study - Patel, Yash R (Clin Nutr, 2016)
BACKGROUND & AIMS: The relationship between healthy lifestyle factors and mortality in people with type 2 diabetes is unclear. The purpose of this study was to examine whether healthy lifestyle factors are associated with mortality in people with type 2 diabetes. METHODS: We prospectively studied 1,163 men with type 2 diabetes from the Physicians’ Health Study. Lifestyle factors consisted of currently not smoking, moderate drinking (1–2 drinks/day), vigorous exercise (1+/week), BMI <25 kg/m(2), and being in the top 2 quintiles of the alternate healthy eating index-2010 (AHEI-2010). Multivariate cox regression models were used to estimate hazard ratios (95% confidence intervals) of mortality. RESULTS: At baseline, average age was 69 years and mean follow up was 9 years. About 22% of study participants had ≤1 healthy lifestyle factor, 37% had two, 29% had three, and 12% had four or more healthy lifestyle factors. An inverse relationship was found between the number of lifestyle factors and total mortality. Compared with participants who had ≤1 healthy lifestyle factor, the risk of death was 42% (95% CI; 19%–58%) lower for those with two healthy lifestyle factors, 41% (95% CI; 18%–58%) lower for those with three, and 44% (95% CI; 12%–64%) lower for those with 4 or more healthy lifestyle factors. CONCLUSION: Adherence to modifiable healthy lifestyle factors is associated with a lower risk of death among adult men with type 2 diabetes. Our study emphasizes the importance of educating individuals with diabetes to adhere to healthy lifestyle factors.